Japan : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1995)
This paper reviews economic developments in Japan during the 1990s. The paper focuses on the weak recovery that began in 1994, against the background of the long and deep recession from mid-1991 to late 1993. Output and labor market developments are described. The paper examines the sharp deterioration in the fiscal position, including the effects of fiscal policy actions, and discusses the progressive easing of monetary policy since 1991. External sector developments are also analyzed, followed by an overview of trade and structural policies.